Interpreting environmental changes from radionuclides and soil characteristics in different landform contexts of Elephant Island (maritime Antarctica). (22nd May 2018) - Navas, Ana; Serrano, Enrique; López‐Martínez, Jerónimo; Gaspar, Leticia; Lizaga, Ivan
Abstract: Soils in ice‐free areas of Elephant Island (South Shetland Islands) have been forming since the last deglaciation following the glacial retreat that started in the area probably later than 9.7–5.5 ka. In paraglacial landscapes, landforms and processes in transition from glacial to nonglacial conditions are experiencing rapid environmental adjustments under conditions of climate change. Soils are highly sensitive and can be good descriptors of these transitional changes. A soil sampling campaign was undertaken for characterizing soils developed on moraines and marine platforms, underlain by metamorphic rocks and with distinctive periglacial features. Eight soil profiles were sampled to investigate the processes involved in their development and the relations with main landforms and processes of ice retreat. The stony Cryosols with mosses and lichens coverage are developed in permafrost environment with an active layer depth of 15–150 cm. Soil organic C content (0.16–1.6%) and large variations of P, K and N contents are related to ornithogenic activity. Soils on moraines and platforms show differences that reflect the more recent exposure of moraines that preserve most the characteristics of the parent material. More vegetated soils on platforms show 137 Cs and 210 Pbex activities (11 and 25 Bq kg −1, respectively) at the topsoil whereas absence of 137 Cs and depleted levels of 210 Pbex occurred in more recently exposed and less developed soils on moraines. Fallout radionuclides are good tracers for identifying characteristics of soil development and providing information on environmental changes of interest to understand the soil response to actual changes in unstable paraglacial environments.